Flower abortion and yield of processing tomato according to irrigation depths - Silva,Cícero J. da (2021)
HIGHLIGHTS The number of flowers, the abortion rate, and the number of fruits per flower cluster directly influence processing tomato yield. Deficient or excessive irrigation levels impair flowering and increase the abortion of flowers of the processing tomato. Irrigation management is essential for the yield of processing tomato crops from the Brazilian Cerrado.